Order, materiality and urban space in the early modern kingdom of Sweden - Laitinen, Riitta, author. Link
1 online resource
Keywords: Our corporeality and immersion in the material world make us inherently spatial beings, and the fact that we all share everyday experiences in the global physical environment means that community is also spatial by nature. This book explores the relationship between the seventeenth-century townspeople of Turku, Sweden, and their urban surroundings. Riitta Laitinen offers a novel account of civil and social order in this early modern town, highlighting the central importance of materiality and spatiality and breaking down the dichotomy of public versus private life that has dominated traditional studies of the time period.